2006
DOI: 10.2527/2006.841125x
|View full text |Cite
|
Sign up to set email alerts
|

Performance responses and indicators of gastrointestinal health in early-weaned pigs fed low-protein amino acid-supplemented diets1

Abstract: The effects of low-protein AA-supplemented diets on piglet performance, visceral organ mass, incidence of diarrhea, intestinal microbial population, and fermentation were studied in a 3-wk trial. After a 7-d adaptation period, 96 piglets (approximately 6.2 kg of initial BW) were assigned to 4 corn-wheat, soybean meal-based dietary treatments in a completely randomized design to give 6 replicate pens per treatment (n = 4 piglets per pen). The treatments were a control wheat-corn-soybean meal-based phase I diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
219
7
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(263 citation statements)
references
References 18 publications
31
219
7
6
Order By: Relevance
“…PUN concentration is mostly dependent on the amounts and balance of AA (Nyachoti et al, 2006;Yue and Qiao, 2008). Previous studies have also reported that there were reductions in PUN concentration by feeding low-CP diets TLR = toll-like receptor; MyD88 = myeloid differentiation factor 88; TRAF-6 = TNF receptor-associated factor 6; NF-κB = nuclear factor kappa B; TOLLIP = toll-interacting protein; IL-1β = interleukin-1 beta.…”
Section: Low-protein Diet Affects Immune Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…PUN concentration is mostly dependent on the amounts and balance of AA (Nyachoti et al, 2006;Yue and Qiao, 2008). Previous studies have also reported that there were reductions in PUN concentration by feeding low-CP diets TLR = toll-like receptor; MyD88 = myeloid differentiation factor 88; TRAF-6 = TNF receptor-associated factor 6; NF-κB = nuclear factor kappa B; TOLLIP = toll-interacting protein; IL-1β = interleukin-1 beta.…”
Section: Low-protein Diet Affects Immune Functionmentioning
confidence: 99%
“…It is well documented that reducing dietary CP level from 16% to 12%, supplemented with indispensable amino acids (IAA), could maintain similar growth performance as pigs fed control diet (Figueroa et al, 2002 andKerr et al, 2003). In addition, a moderate reduction of dietary CP level has been shown to decrease the harmful microbial metabolites in the digesta such as ammonia N (Nyachoti et al, 2006;Opapeju et al, 2008), as well as improving the villous morphology of weaned piglets (Gu and Li, 2004;Opapeju et al, 2008). In contrast, several studies have shown that pig growth performance can decrease when the dietary CP level is reduced by more than 4% , even though supplemented with IAA (Powell et al, 2011;Gloaguen et al, 2014), moreover, poor intestinal growth and morphology, reduced disaccharidase activities in small intestine were observed in pigs receiving extremely low-CP diets Yue and Qiao, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, focus has been shifted to finding alternative, nonpharmaceutical, strategies for the prevention and control of PWC, such as the manipulation of dietary ingredients, to minimise substrate availability to ETEC within the distal small intestine and modification of management practices. It has been suggested that PWC is sensitive to dietary protein supply and that it may be possible to limit the extent of PWC by lowering the protein content of the diet (Prohá szka and Baron, 1980;Nyachoti et al, 2006;Wellock et al, 2006). However, Nyachoti et al (2006) and Wellock et al (2006) also noted detrimental effects on performance with a decrease in protein supply.…”
Section: Introductionmentioning
confidence: 98%
“…It has been well accepted that the use of crystalline amino acids (AA) in low crude protein (CP) diets can reduce the nitrogen excretion in swine manure by more than 35% (Le et al 2006;Nyachoti et al 2006).…”
Section: Introductionmentioning
confidence: 99%